BIOTECHNOLOGY FOR OBTAINING BIOLOGICALLY ACTIVE SUBSTANCES FROM MICROALMS (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article analyzes modern biotechnological methods for obtaining biologically active substances (BAUs) from microalgae, their nutritional and pharmaceutical value, as well as their industrial applications. The increasing global demand for natural and safe products has made microalgae biotechnology one of the most promising areas. The article provides a detailed description of the technological stages of cultivation, biomass collection, and extraction processes.
Keywords: Microalgae, Chlorella, Spirulina (Arthrospira), and Haematococcus, Haematococcus pluvialis, Dunaliella salina.